(3eLehYI CTYGQs - (3eLghds
(3ChdgG (B:s
(3jG YGPdj ajef oCMoH LgGdkI JGddg eG oCPfj dZjQc SGeYg s
(3BNQgG (B:s
(3fXQhG Edi GdOfjG JaqQ dCgdgG HhUGdgG, hJcoqQ aj GdEHYGO s
(3efgG dQGHYI GdYOhjI hZjQgGs
(3hHgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3LeYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdCOHs